驱蚊、灭蚊植物资源及其应用前景分析 - 汪秀芳; 薛淋淋; 叶碎高; 李振基 (2013)
蚊虫吸食人血、传播疾病,严重危害人类健康。长期以来,化学合成杀虫剂由于驱灭蚊虫的效果好、持续时间长,一直占据主要地位,但长期使用化学合成杀虫剂,不仅可使蚊虫产生抗药性,而且还会造成环境污染,因此环境友好型的蚊虫防治手段日益受到人们的关注。该论文基于蚊虫与水、植物等环境因素关系的分析,阐述了植物在防治蚊虫方面的潜力;概括了我国的驱蚊、灭蚊植物资源及开发利用现状;探讨了驱蚊、灭蚊植物在防治蚊虫产品开发、生态保健型园林绿地和健康湿地系统建设等方面应用情况并展望了驱蚊、灭蚊植物资源开发利用的广阔前景,以期为蚊虫的生态防治提供新思路。 Mosquitoes are seriously harmful to human health for transmitting some mortal diseases.Among all methods of mosquito control,synthetical insecticides are the most popular for their effective and durable effects.But there is high resistance of mosquito to insecticides and heavy environmental pollution as a result of long-term use of synthetical insecticides.Thus,eco-friendly prevention measures are taken into the agenda.Based on the relationship between mosquito and the environment,such as water and plant,this paper discussed the potential of controlling mosquito by plants,and summarized the resource of mosquito-repellent and mosquitocidal plants in China.We emphasized the wide application prospect of mosquito-repellent and mosquitocidal plants in mosquito control products,and in modern protective greenlands and healthy wetland ecosystems,which provided a new idea for ecological management of mosquito.